Hypo- and dysgeusia in oral frailty - V.A., Mogilev (Magyar Gerontológia, 2023)
The purpose of the research is to identify the patterns and dependence of taste formation in elderly and senile people on various factors and dental status, as well as the development of methods for early diagnosis and prevention.